Magnetite-Activated Carbon Composite to Reduce Pollutant: Review - Rafli, Muhammad; Wahyuni, Reza Mega; Zahiro, Nilna Muna; Dasna, I Wayan (Indonesian Journal of Chemical Research, 2021)
Pollution is a serious environmental problem. One of the causes of pollution is the presence of heavy metals. Besides heavy metals, there are plastics that cause serious problems in the environment because they are difficult to decompose. These two problems appear an idea about synthesizing activated carbon-magnetite (Fe3O4) composite based on polyethylene that can absorb heavy metals. The method used literature review of relevant articles. This study examines the properties of magnetite both physical and chemical along with the applications and benefits of magnetite in daily life. This study can become a new perspective effort to reduce heavy metals pollution using plastic waste as a composite with Fe3O4